Adamts10 controls transforming growth factor β family signaling that contributes to retinal ganglion cell development - Wareham, Lauren K.; Whitener, Amy E.; Wu, Hang-Jing; Wu, Shu-Yu; Mchaourab, Hassane S.; Mortlock, Douglas P.; Kuchtey, Rachel W.; Kuchtey, John (Frontiers in Molecular Biosciences, 2022)
Although mutations in ADAMTS10 have long been known to cause autosomal recessive Weill-Marchesani Syndrome which is characterized by short stature and ocular abnormalities, more recent work has shown that certain mutations in ADAMTS10 cause glaucoma in dogs. In humans, glaucoma is the leading cause of irreversible vision loss that affects tens of millions of people world-wide. Vision loss in glaucoma is a result of neurodegeneration of retinal ganglion cells that form the inner-most layer of the retina and whose axons form the optic nerve which relays visual information to the brain. ADAMTS10 contributes to the formation of microfibrils which sequester latent transforming growth factor β (TGFβ) thereby controlling its activation and bioavailability. Among its many biological functions, TGFβ promotes the development of retinal ganglion cells and is also known to play other roles in glaucoma pathogenesis. The aim of this study was to test the hypothesis that ADAMTS10 plays a role in retinal ganglion cell development through regulation of TGFβ signaling. Zebrafish embryos carrying either a fluorescent reporter that labels retinal ganglion cells, or a fluorescent reporter of pSmad3-mediated TGFβ family signaling, were injected at the one-cell stage with either a morpholino oligonucleotide designed to block translation of adamts10 mRNA or with a single guide RNA and Cas9 protein for CRISPR/Cas9-mediated disruption of exon 1 of adamts10. Retinal ganglion cell reporter fluorescence in whole embryos and cryosections were determined 48 - 72 hours later. MO and CRISPR/Cas9 targeting of adamts10 expression reduced retinal ganglion cell reporter fluorescence and prevented formation of an ordered retinal ganglion cell layer. Targeting adamts10 expression also drastically reduced constitutive TGFβ signaling in the eye. Direct inhibition of the TGFβ receptor reduced retinal ganglion cell reporter fluorescence and prevented retinal lamination, similar to the effect of targeting adamts10 expression. These findings unveil a previously unknown role for Adamts10 in retinal ganglion cell development and suggest that the developmental role of Adamts10 is mediated by active TGFβ family signaling. In addition, our results show for the first time that Adamts10 is necessary for pSmad3-mediated constitutive TGFβ family signaling.